Mapa da atividade industrial de Belém do Pará: análise temporal e espacial - FERREIRA, Rosivaldo Galvão (2023)
Located in the northern region of Brazil, the city of Belém do Para had its economic peak in the golden age of rubber, when the first industrial center of the city was implemented in the neighborhood of the redoubt. After a series of factors that led the companies to a process of decay that culminated in the closure of many of them, the Redoubt ceased to be the industrial center of the city. The creation of new criteria for the use and occupation of urban land, associated with urban growth, gave rise to a new configuration of space, and in this context industrial activity became an unknown quantity. The problem of this work is based on the lack of georeferenced data of industrial enterprises in the city of Belém do Pará. Therefore, the objective of this work is to show the existence of an industrial activity through a map with the spatialization of industrial enterprises. Having as a methodology the bibliography research, the fieldwork and the use of geoprocessing techniques with emphasis on the use of a Geographic Information System – GIS.